Tanggapan Tanaman Kedelai terhadap Inokulasi Rhizobium - OKTI PURWANINGSIH; DIDIK INDRADEWA; SITI KABIRUN; DJAFFAR SHIDDIQ (Fakultas Pertanian Universitas Udayana, 2012)
Nitrogen is one important element in plant growth. In soybean crop nitrogen requirement can bemet from the fixation of nitrogen which is the result of symbiosis between rhizobium bacteria withsoybean. A study on the relationship between soybean cultivar and rhizobium inoculation was conductedin Banguntapan Bantul Yogyakarta on regusol soils. Research aimed the responses of soybean cultivarof rhizobium inoculation. This research is a pot experiment that tested the response of 16 soybeancultivars of rhizobium inoculation. The sixteen cultivars consisted of 12 superior cultivars and 4 localcultivars. Before planting soybean seeds were inoculated with legin. Land used first sterilized usingautoclaves. Determination of soybean cultivars into four categories based on agronomic charactersnodule number, nodule dry weight, canopy N content, nitrogenase activity and grain yield components(seed dry weight). The study demonstrated that (1) Cultivars Anjasmara, Sibayak, Surya, Gepak yellow,Galunggung, Argomulyo and Baluran provide a response to rhizobium inoculation in the form of increasednitrogen fixation and grain yield (2) rhizobium inoculation on Tanggamus cultivars can increase nitrogenfixation but not followed by an increase in grain yield (3) rhizobium inoculation in cultivar Malabar,Seulawah and Petek not increase nitrogen fixation but can increase grain yield (4) rhizobium inoculationin cultivar Ijen, Sinabung, Wilis, Grobogan, and Garut not increase nitrogen fixation and grain yield.